2014
DOI: 10.1080/13540602.2014.885704
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration to teach English language learners: opportunities for shared teacher learning

Abstract: This study examines collaboration between English for Speakers of Other Languages (ESOL) teachers and content-area elementary school teachers, and makes the case for conceptualising teacher collaboration as an opportunity for shared teacher learning. Using a sociocultural theoretical lens, this study examines how three pairs of elementary teachers and ESOL specialists used and constructed tools for collaboration, which mediated and made visible teachers' learning processes. Employing interpretive enquiry and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 40 publications
(46 reference statements)
3
28
0
Order By: Relevance
“…In fact, it appears that collaboration among educators (teachers, coaches, and learning communities) is a promising approach for our field. Several studies document positive outcomes for such collaborations, all focused on improved planning and practice for content teachers working with multilingual students (e.g., Baecher, Knoll, & Patti, 2016;Chien, 2013;Martin-Beltrán & Peercy, 2014;Peercy, Martin-Beltrán, Silverman, & Nunn, 2015;Rodríguez, Abrego, & Rubin, 2014;Russell, 2014). Additionally, Jimenez-Silva and Olson (2012) found teacher learning communities to be valuable for supporting pre-service teacher learning about working with multilingual learners.…”
Section: Teacher Learning Mattersmentioning
confidence: 99%
“…In fact, it appears that collaboration among educators (teachers, coaches, and learning communities) is a promising approach for our field. Several studies document positive outcomes for such collaborations, all focused on improved planning and practice for content teachers working with multilingual students (e.g., Baecher, Knoll, & Patti, 2016;Chien, 2013;Martin-Beltrán & Peercy, 2014;Peercy, Martin-Beltrán, Silverman, & Nunn, 2015;Rodríguez, Abrego, & Rubin, 2014;Russell, 2014). Additionally, Jimenez-Silva and Olson (2012) found teacher learning communities to be valuable for supporting pre-service teacher learning about working with multilingual learners.…”
Section: Teacher Learning Mattersmentioning
confidence: 99%
“…The teachers also stated a desire to have opportunities to exchange ideas about strategies to use in their classrooms. Martin‐Beltran and Peercy () support this suggestion by stating that collaboration framed as shared teacher learning can be facilitated through the use of tools such as rubrics, assessments, curriculum guides, lesson plans, and collaborative dialogue. This time for collaborative dialogue will allow teachers to negotiate their implementation of the curriculum in the ELD block and make appropriate adaptations to meet students' needs (Pease‐Alvarez et al., ).…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
“…This schoolwide focus means that efficacy throughout the school will increase along with individual perceptions of efficacy (Téllez & Manthey, ). This is because teacher learning tends to increase through collaborative measures (Martin‐Beltran & Peercy, ). Four of the five participants indicated that ELL instructional practices should be integrated throughout the school day.…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graziano and Navarrete 2012;Martin-Beltran and Peercy 2014;Plank 2011) but also as a factor of job satisfaction and increase in motivation(Birrell and Bullough Jr. 2005). Many teachers across different countries and disciplines reported feeling energised and reinvigorated as a result of co-teaching (Plank 2011; Graziano and Navarrete 2012).…”
mentioning
confidence: 99%